STRATEGIC DIRECTIONS OF THE STATE REGULATION OF COMPETITIVE RELATIONSHIP TO STRENGTHENING REQUESTS AND PROPOSALS IN REGIONAL MARKETS OF HOUSING IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
This article outlines the problematic issues faced by the residential real estate market in the current state of the country. The features of providing regional markets of residential real estate with the proper level of demand and supply in the market are investigated. The main aspects that influence it are determined. The strategic directions of regulation at all levels of competitive relations between market participants are proposed by stimulating demand and supply on the regional markets of primary and secondary residential real estate in Ukraine. The basis of these is privatization and activation processes, a system for improving housing savings and long-term mortgage systems, restoration of housing stock, support for communal property, stimulation of various forms of individual property, etc. In accordance with the results of our study, it is evident that the housing problem is present in almost all regions of our country. This situation is explained by the almost complete absence of the necessary support from the state in the field of investment in housing. As a result, we can conclude that the main factors hindering the proper development of the residential real estate market in the regional markets of Ukraine, including the following: a steady decrease in the volume of public housing financing, a decrease in the volume of state housing construction, ineligible interest rates on mortgage loans , constant increase of market value of building materials and services; rising energy prices; low level of solvency of the consumer sector. It is summarized that the strengthening of the production of building materials at the industrial level, the reform of the housing construction industry in the state deserves special attention. At the same time, we note that the specialization of construction processes, which focuses on the domestic consumption market, provides the necessary foundations for a much wider range of applications for small business. At the same time, raising the level of employment, reducing the distance and volume of transport of construction products will contribute to the development of competitive relations in the regional markets of residential real estate.
Keywords: housing, the housing market, demand, supply, stimulation, directions of market development, the construction market, primary and secondary market